2014
DOI: 10.3390/md12052408
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Effects of Synthetic Derivatives of Polymeric Alkylpyridinium Salts from the Marine Sponge, Reniera sarai

Abstract: Polymeric 3-alkylpyridinium salts (poly-APS) are among the most studied natural bioactive compounds extracted from the marine sponge, Reniera sarai. They exhibit a wide range of biological activities, and the most prominent among them are the anti-acetylcholinesterase and membrane-damaging activity. Due to their membrane activity, sAPS can induce the lysis of various cells and cell lines and inhibit the growth of bacteria and fungi. Because of their bioactivity, poly-APS are possible candidates for use in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…These sessile organisms from the phylum Porifera produce several secondary metabolites with defensive functions against pathogens, predators, or for space competition. Many of these bioactive molecules have been used as drug leads , and some synthetic derivatives have been approved for clinical use or have progressed to Phase II/III clinical trials …”
Section: Introductionmentioning
confidence: 99%
“…These sessile organisms from the phylum Porifera produce several secondary metabolites with defensive functions against pathogens, predators, or for space competition. Many of these bioactive molecules have been used as drug leads , and some synthetic derivatives have been approved for clinical use or have progressed to Phase II/III clinical trials …”
Section: Introductionmentioning
confidence: 99%
“…Its application in medicine led to the synthesis of a series of synthetic analogs with different degrees of polymerization and different lengths of alkyl chains (Houssen et al, 2010). Recently, the effects of some of these synthetic analogs due to their AChE inhibitory potency were studied on the skeletal neuromuscular transmission (reviewed in Grandic and Frangez, 2014). Experiments on skeletal neuromuscular preparations revealed that APS12-2, a non-competitive AChE inhibitor which was previously shown to be selectively cytotoxic toward NSLC cells in vitro, is a potent antagonist of skeletal muscle nAChRs (Grandic et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic analogs of Poly-3-APS, such as APS12-2, APS3 (Grandic et al, 2011;Grandic et al, 2013), APS8 (unpublished data) and structurally related compounds, are promising new chemotherapeutic agents that exhibit very low in vivo toxicity in experimental animals. Recently, the effects of some of these synthetic analogs possessing potent AChE-inhibitory properties were studied on neuromuscular transmission in skeletal muscle (reviewed in Grandic and Frangez, 2014) to avoid unwanted peripheral side effects that could appear in patients treated with some AChE inhibitors. APS12-2 acts as a potent non-competitive AChE inhibitor with an inhibitory constant (K i ) of 34 × 10 −3 nM (Houssen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This means that the activity only increases to a certain tail length and then decreases. The cut-off effect of the membrane active compounds (which penetrate to the membrane and disrupt its architecture) has been well documented [14,19,20,[36][37][38][39][40][41][42][43][44].…”
Section: Chemistrymentioning
confidence: 99%
“…It can only be speculated whether the different courses of dependences of bactericidal activities against S. aureus ATCC 29213/MRSA SA 3202 (MRSA3) from isolates MRSA1/MRSA2 could be due to their differences in the composition of bacterial membranes [55][56][57][58]. The effect of changing the length of the hydrocarbon tail affecting the extent of antimicrobial activity of the compounds has been discussed (e.g., [36,37,[39][40][41][42][43][44]59,60]). The decrease in biological activity at a higher chain length as a cut-off effect is discussed above.…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%